(untitled) (Human Computation, 2014)
Crowdsourcing is a business model which allows practitioners to access a rather cheap and scalable workforce. However, due to loose worker-employer relationships, skill diversity of the crowd and anonymity of participants, it tends to result in lower quality compared to traditional ways of doing work. Thus crowdsourcing practitioners have to apply certain techniques to make sure that the end product complies with the quality requirements. Quality assurance techniques impact project costs and schedules. A well-defined methodology is needed to estimate these impacts in order to manage the crowdsourcing process effectively and efficiently. This paper introduces cost models of common quality assurance techniques that may be applied in crowdsourcing and describes a proposed cost of quality approach for analyzing quality related costs.